Секрет салона красоты - Вильмонт Екатерина Николаевна (Большая книга детективов Е. Вильмонт, 2008)
Экземпляры: (20181015) / Инвентарный номер: 33683 / Цена: 96.70 / Сис.шифр: Р2 / Авт.знак: В 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6